Sorption/desorption of phenanthrene and ofloxacin by microbial-derived organic matter-mineral composites - Li, Fangfang; Yan, Qiuling; Li, Zhongwen; Tan, Zhicheng; Li, Yuxuan; Wang, Siyao; Guo, Jiawen; Peng, Hongbo; Wang, Lin (Frontiers in Environmental Science, 2024)
Introduction Soil organic matter plays an important role in the long-term “locking” of organic contaminants in soil environment. Recently, microbial-derived organic matter have been recognized as essential components of stabilized soil carbon pools. However, the contribution of microbial-derived organic matter to sorption of organic contaminants remains unclear. Methods Here, we obtained microbial-derived organic matter-mineral composites by inoculating model soil (a mixture of hematite and quartz sand (FQ) or montmorillonite and quartz sand (MQ)) with natural soil microorganisms and different substrate-carbon (glycine (G), glucose (P), or 2, 6-Dimethoxyphenol (B)), which were named GF, PF, BF, GM, BM, and PM, respectively. Batch sorption/desorption experiments were conducted for phenanthrene (PHE) and ofloxacin (OFL) on the composites. Results and Discussion The composites cultured with 2,6-dimethoxyphenol had the highest carbon content (0.98% on FQ and 2.11% on MQ) of the three carbon substrates. The carbon content of the composites incubated with MQ (0.64%–2.11%) was higher than that with FQ (0.24%–0.98%), indicating that montmorillonite facilitated the accumulation of microbial-derived organic matter owing to its large specific surface area. The sorption of PHE by microbial-derived organic matter was mainly dominated by hydrophobic partitioning and π-π conjugation, whereas the sorption of OFL was mainly dominated by hydrophobic hydrogen bonding and π-π conjugation. The sorption of OFL onto the composites was more stable than that of PHE. Microbial-derived organic matter -mineral composites can reduce the risk of organic contaminant migration in soil, particularly ionic organic contaminants.